Pengaruh Viral Marketing Dan Purchase Intention Terhadap Brand Equity Kasus Pada Kampanye Produk Azzarine - Marchetia, Alva Ade; Romadhoni , Buyung; M. Hidayat (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The purpose of this study is to determine the effect of viral marketing and purchase intention on brand equity in the Azzarine product campaign. The sample of this study was 100 people. The sampling technique used characteristics. The type of data used in this study is primary data with multiple regression methods and using SPSS 25 for windows. The results of the study indicate that viral marketing has a positive and insignificant effect on brand equity and purchase intention has a positive and insignificant effect on brand equity in the Azzarine product campaign. The need to increase viral marketing and purchase intention in order to improve brand equity as a whole.